Positive electrode slurry composition for lithium secondary battery, positive electrode and lithium secondary battery including the same
The introduction of LiCMC and a carbodiimide-based compound into the positive electrode slurry composition addresses the issue of low thixotropy in conventional slurries, resulting in improved flowability and uniform coating, which enhances the charge/discharge performance of lithium secondary batteries.
Patent Information
- Application Number
- JP2023531082
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-07-08
- Filing Date
- 2022-07-07
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2042-07-07
AI Technical Summary
Conventional positive electrode slurries for lithium-sulfur secondary batteries exhibit low thixotropy, leading to inadequate flow performance during the solution coating process, which results in non-uniform positive electrode active material layers and compromised charge/discharge performance.
A positive electrode slurry composition is developed, incorporating lithiated carboxymethyl cellulose (LiCMC) as a thickener and a carbodiimide-based compound as an additive, which enhances the flowability and thixotropy of the slurry, allowing for uniform coating even with varying coating speeds.
The improved slurry composition achieves sufficient flowability and thixotropy, enabling the formation of a uniform positive electrode active material layer, thereby enhancing the charging and discharging performance of lithium secondary batteries.
Smart Images

Figure 0007670824000003 
Figure 0007670824000004 
Figure 0007670824000001
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 2021-0089719 dated July 8, 2021, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference.
[0002] The present invention relates to a positive electrode slurry composition for a lithium secondary battery, and a positive electrode and a lithium secondary battery containing the same. [Background technology]
[0003] Recently, with the rapid development of electronic devices and electric vehicles, the demand for secondary batteries is increasing. In particular, with the trend toward smaller and lighter portable electronic devices, there is a growing demand for secondary batteries having high energy density that can meet the trend.
[0004] Among secondary batteries, lithium-sulfur secondary batteries use a sulfur-based compound having a sulfur-sulfur bond as a positive electrode active material and a carbon-based material in which an alkali metal such as lithium or a metal ion such as lithium ion is inserted and removed, or silicon or tin that forms an alloy with lithium as a negative electrode active material. Specifically, the lithium-sulfur secondary battery stores and generates electrical energy by utilizing an oxidation-reduction reaction in which the oxidation number of sulfur is increased and the sulfur-sulfur bond is broken during discharge, which is a reduction reaction, and the oxidation number of sulfur is increased and the sulfur-sulfur bond is formed again during charge, which is an oxidation reaction.
[0005] In particular, sulfur used as a positive electrode active material in lithium-sulfur secondary batteries has a theoretical energy density of 1,675mAh / g, which is about five times higher than the positive electrode active material used in existing lithium secondary batteries, making it possible for the battery to achieve high output and high energy density. In addition, sulfur has the advantages of being inexpensive, abundant in reserves, easy to supply and demand, and environmentally friendly, and is therefore attracting attention as an energy source for medium and large devices such as electric vehicles as well as portable electronic devices.
[0006] Sulfur has an electrical conductivity of about 5x10 -30 Since sulfur is an insulator with no electrical conductivity at 1000 S / cm, it is difficult to move electrons generated in electrochemical reactions. Therefore, it is used as a sulfur-carbon composite by combining it with an electrically conductive material such as carbon that can provide electrochemical reaction sites.
[0007] In order to use the sulfur-carbon composite as a cathode material, a slurry is prepared by using the sulfur-carbon composite, a conductive material, a binder, and a thickener, and then the slurry is applied to a current collector in a slurry process to manufacture a cathode.
[0008] However, the conventional positive electrode slurry for lithium-sulfur secondary batteries has low thixotropy, and sufficient flowability is not guaranteed when the positive electrode slurry is applied to a solution coating process. Therefore, when preparing the positive electrode slurry, a dispersion agent and / or a rheology modifier that is compatible with the sulfur-carbon composite, which is the positive electrode active material, is used, but the use of these agents does not significantly change the flowability, and the use of the dispersion agent and / or the rheology modifier weakens the charge / discharge performance.
[0009] Meanwhile, recent research results have been published on improving the flowability of a positive electrode slurry by using a carboxymethyl cellulose-based material as a binder during preparation of a positive electrode composition.
[0010] For example, Korean Patent Publication No. 2016-0071740 includes carboxymethyl cellulose (CMC) as a binder when preparing a positive electrode composition in order to provide an aqueous positive electrode composition that provides stable and flexible electrode plate characteristics. However, when only carboxymethyl cellulose is used as a binder, a slurry with low thixotropy does not spread properly when the coating speed changes in the slurry coating process, which causes a problem that a positive electrode active material layer cannot be formed uniformly.
[0011] Lei Qui et al. (Carbohydrate polymers, Vol. 112, (2014) pp. 532-538) discloses a positive electrode composition for lithium secondary batteries containing lithiated carboxymethyl cellulose (LiCMC) as a binder. However, when only lithiated carboxymethyl cellulose is used as a binder, the thixotropy is weak during the preparation of the positive electrode slurry, and when the coating speed changes during the coating process of the positive electrode active material layer, the positive electrode composition cannot be appropriately adapted, resulting in a problem that the positive electrode active material layer cannot be uniformly formed.
[0012] Thus, research is being conducted to improve the rheological properties of the positive electrode slurry so as to improve the processability during the manufacture of a positive electrode for a lithium secondary battery and the charge / discharge performance of the manufactured lithium secondary battery. However, the positive electrode slurries developed to date have not been able to show significant effects in terms of improving the processability and battery performance during the manufacture of a positive electrode for a lithium secondary battery. [Prior art documents] [Patent documents]
[0013] [Patent Document 1] Korean Patent Publication No. 2016-0071740 [Patent Document 2] Lei Qui et al.(Carbohydrate polymers, Vol.112,(2014)pp.532-538) Summary of the Invention [Problem to be solved by the invention]
[0014] As a result of extensive research to solve the above problems, the present inventors have found that when a thickener, lithiated carboxymethyl cellulose (LiCMC), and an additive, a carbodiimide-based compound, are mixed into a positive electrode slurry composition for a lithium secondary battery, the flowability of the positive electrode slurry composition is improved, and a good quality positive electrode active material layer can be formed even if the coating speed is changed in a coating process of the positive electrode slurry composition during the manufacture of the positive electrode.
[0015] Therefore, an object of the present invention is to provide a positive electrode slurry composition for a lithium secondary battery that has excellent flowability and can flexibly respond to variable process conditions during slurry coating.
[0016] Another object of the present invention is to provide a positive electrode prepared using the positive electrode slurry composition having good flowability, and a method for preparing the same.
[0017] It is still another object of the present invention to provide a lithium secondary battery including a positive electrode prepared using the positive electrode slurry composition having good flowability. [Means for solving the problem]
[0018] In order to achieve the above object, the present invention provides a positive electrode slurry composition for a lithium secondary battery, comprising a positive electrode active material, a conductive material, a binder, a thickener, an additive, and a solvent, wherein the thickener comprises lithiated carboxymethyl cellulose (LiCMC), and the additive comprises a carbodiimide-based compound.
[0019] The present invention also provides a positive electrode for a lithium secondary battery, comprising: a positive electrode current collector; and a positive electrode active material layer formed on one surface of the positive electrode current collector, the positive electrode active material layer being formed from the positive electrode slurry composition.
[0020] The present invention also provides a method for manufacturing a positive electrode for a lithium secondary battery, the method including: (S1) coating one surface of a positive electrode current collector with the positive electrode slurry composition; (S2) drying the coating layer formed in (S1); and (S3) rolling the coating layer to form a positive electrode active material layer.
[0021] The present invention also provides a lithium secondary battery comprising the positive electrode, the negative electrode, a separator, and an electrolyte. Effect of the Invention
[0022] The positive electrode slurry composition according to the present invention has flowability sufficient to flexibly accommodate changes in coating speed during a coating process, and thus a positive electrode having a uniform positive electrode active material layer formed on a positive electrode current collector can be manufactured using the positive electrode slurry composition.
[0023] In addition, a lithium secondary battery including a positive electrode prepared using the positive electrode slurry composition having good flowability exhibits improved charge / discharge performance. [Brief description of the drawings]
[0024] [Figure 1] 1 is a graph showing the change in shear stress depending on the shear rate for the positive electrode slurry compositions of Example 1 and Comparative Example 1. [Diagram 2] 1 is a graph showing charge / discharge characteristics of the lithium-sulfur secondary batteries of Example 1 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] The present invention will now be described in further detail to aid in the understanding of the present invention.
[0026] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a meaning and concept that corresponds to the technical idea of the present invention, based on the principle that the inventor can appropriately define the concept of the term in order to best describe his / her invention.
[0027] The term "thixotropy" as used herein means the property of a material whereby the viscosity increases when no shear stress is applied to it and decreases when a shear stress is applied to it.
[0028] The term "solid content" used in this specification generally refers to the positive electrode active material, conductive material, binder, thickener, and additives remaining after removing the solvent from the positive electrode slurry composition for lithium secondary batteries.
[0029] Positive electrode slurry composition for lithium secondary battery The present invention relates to a positive electrode slurry composition having flowability sufficient to flexibly accommodate a change in coating speed during a coating process for forming a positive electrode active material layer during the manufacture of a positive electrode for a lithium secondary battery. Here, "adaptable" means that when the coating speed is increased, the viscosity of the positive electrode slurry composition decreases to allow the positive electrode slurry composition to be uniformly coated at a high coating speed due to an increase in shear stress applied to the positive electrode slurry composition between a current collector and a coating bar on which a coating material is coated, and when the coating speed is decreased, the viscosity of the positive electrode slurry composition increases to allow the positive electrode slurry composition to be uniformly coated at a low coating speed.
[0030] The positive electrode slurry composition for a lithium secondary battery according to the present invention includes a positive electrode active material, a conductive material, a binder, a thickener, an additive, and a solvent, the thickener includes lithiated carboxymethyl cellulose (LiCMC), and the additive includes a carbodiimide-based compound.
[0031] The positive electrode slurry composition for lithium secondary batteries contains a carbodiimide-based compound as an additive, and thus exhibits improved thixotropy and improved storage properties. In the case of a slurry with increased thixotropy, the ability to maintain viscosity during storage without shear stress is increased, and the change in the slurry composition between the upper and lower parts of the slurry over time is small, improving storage properties. If a change in the composition of the slurry between the upper and lower parts of the slurry occurs, the internal composition of the slurry will differ during slurry coating, and a coating layer with an uneven composition may be formed.
[0032] Hereinafter, the present invention will be described in more detail, focusing on each component of the positive electrode slurry composition for lithium secondary batteries.
[0033] In the present invention, the positive electrode active material is elemental sulfur (S8), Li2S n (n ≧ 1, n is an integer), organic sulfur compounds, and carbon-sulfur polymers [(C2S x ) n , 2.5≦x≦50, n≧2, where x and n are integers. Preferably, the positive electrode active material may include elemental sulfur. For example, the positive electrode active material may be a sulfur / carbon composite, and the sulfur / carbon composite may be an S / CNT composite obtained by using sulfur S and CNT (Carbon Nanotube).
[0034] In addition, the positive electrode active material may be included in an amount of 60 wt% to 97 wt% based on the total weight of the solid content of the positive electrode slurry composition. Specifically, the content of the positive electrode active material may be 60 wt% or more, 70 wt% or more, or 80 wt% or more, and 91 wt% or less, 93 wt% or less, or 97 wt% or less. If the content of the positive electrode active material is less than 60 wt%, the battery capacity of the entire cell may decrease, and if it exceeds 97 wt%, the content of one or more of the conductive material, binder, thickener, and additive, excluding the positive electrode active material, may relatively decrease, and the flowability, conductivity, or physical properties of the positive electrode slurry composition may decrease.
[0035] The conductive material is used to improve electrical conductivity, and is not particularly limited as long as it is an electrically conductive material that does not undergo chemical changes in the lithium secondary battery.
[0036] The conductive material may include at least one selected from the group consisting of carbon black, graphite, carbon fiber, carbon nanotube, metal powder, conductive metal oxide, and organic conductive material. The carbon black may include at least one selected from the group consisting of ketjen black, super P, denka black, acetylene black, and furnace black.
[0037] The conductive material may be included in an amount of 0.01 to 30 wt % based on the total weight of the solid content of the positive electrode slurry composition. Specifically, the content of the conductive material may be 0.01 wt % or more, 2 wt % or more, or 4 wt % or more, and 10 wt % or less, 20 wt % or less, or 30 wt % or less. If the content of the conductive material is less than 0.01 wt %, the conductivity of the positive electrode may decrease, and if it exceeds 30 wt %, the flexibility of the positive electrode may decrease.
[0038] In addition, the binder supports the positive electrode active material on the positive electrode current collector and organically connects the positive electrode active materials to each other to further increase the binding strength therebetween. Any binder known in the art may be used as the binder.
[0039] The binder may be one or a mixture or copolymer of two or more selected from the group consisting of fluororesin-based binders including polyvinylidene fluoride (PVdF) and / or polytetrafluoroethylene (PTFE); rubber-based binders including one or more of styrene butadiene rubber (SBR), acrylonitrile butadiene rubber, and styrene-isoprene rubber; cellulose-based binders including one or more of carboxyl methyl cellulose (CMC), starch, hydroxypropyl cellulose, and regenerated cellulose; polyalcohol-based binders; polyolefin-based binders including one or more of polyethylene and polypropylene; polyimide-based binders; polyester-based binders; acrylic-based binders including acrylic monomers; and silane-based binders. According to one embodiment of the present invention, the binder is preferably a combination of rubber-based binders. In addition, when the compatibility with the carboxymethyl cellulose-based thickener is taken into consideration, the binder may include SBR and / or an acrylic binder.
[0040] The binder may be an emulsion type binder. Generally, the form of the positive electrode binder is not particularly limited and may be a linear polymer form as long as it can bind the components in the positive electrode. However, when the emulsion type binder is used, the positive electrode components can be most effectively bound in a dot-to-dot form, and the adhesive strength is also good. In addition, when the emulsion type binder is used, the solid content of the slurry is increased compared to a linear polymer type binder.
[0041] In addition, the binder may be included in an amount of 0.01 to 30 wt % based on the total weight of the solid content of the positive electrode slurry composition. Specifically, the content of the binder may be 0.01 wt % or more, 1 wt % or more, or 2 wt % or more, and 10 wt % or less, 20 wt % or less, or 30 wt % or less. If the content of the binder is less than 0.01 wt %, the physical properties of the positive electrode, such as the binding force, may decrease, and the positive electrode active material and the conductive material may fall off, and if the content of the binder exceeds 30 wt %, the ratio of the positive electrode active material and the conductive material may relatively decrease, and the battery capacity may decrease.
[0042] In addition, the thickener may provide appropriate viscosity to the positive electrode slurry composition to ensure the stability of the positive electrode slurry composition, and may alleviate re-agglomeration of solids when the positive electrode slurry composition is coated on a positive electrode current collector, thereby improving surface defects.
[0043] The thickener may include lithiated carboxymethyl cellulose (LiCMC), which may be represented by the following Chemical Formula 1:
[0044] [ka]
[0045] In the above formula 1, R is H or CH2COOH, and n is 25 to 2000.
[0046] The LiCMC replaces the metal ions of conventional CMC with Li. The metal ions contained in conventional CMC can act as impurities inside the cell and reduce the performance of the cell, but LiCMC eliminates such impurities inside the cell and contains lithium ions, minimizing the degradation of cell performance caused by impurities.
[0047] In addition, the LiCMC is used together with a carbodiimide compound containing an amino group, which changes the interaction (hydrogen bond) within the slurry, thereby improving the thixotropy in response to shear stress. Specifically, the interaction between the functional group (-OCH2COO- or -OR) of the LiCMC and the functional group (C=N double bond) within the carbodiimide compound by hydrogen bonding increases the thixotropy of the slurry, improving the storage stability of the slurry.
[0048] In addition, the thickener may be included in an amount of 0.5 wt% to 5 wt% based on the total weight of the solid content of the positive electrode slurry composition. Specifically, the content of the thickener may be 0.5 wt% or more, 0.8 wt% or more, or 1 wt% or more, and 2 wt% or less, 3 wt% or less, or 5 wt% or less. If the content of the thickener is less than 0.5 wt%, the positive electrode slurry composition may have low viscosity and flow down like water, making it difficult to coat the positive electrode slurry composition on the positive electrode current collector, and if the content exceeds 5 wt%, the positive electrode slurry composition may be difficult to form a uniform coating layer due to high viscosity and hardness.
[0049] The viscosity of the positive electrode slurry composition is not particularly limited, and may vary depending on the content of the thickener. Taking into consideration the phase stability of the positive electrode slurry composition and ease of the coating process, the viscosity may be 1000 cP or more, or 4500 cP or more at 25° C.
[0050] In addition, the additive may have thixotropy that allows the additive to accommodate a variable coating speed in a coating process in which the positive electrode slurry composition is coated on a positive electrode current collector during the preparation of the positive electrode.
[0051] The additive includes a carbodiimide-based compound, and the carbodiimide-based compound may include at least one selected from the group consisting of 1-ethyl-3-[3-(dimethylamino)propyl]-carbodiimide hydrochloride (EDC), 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, N,N'-diisopropylcarbodiimide, and N,N'-di-tert-butylcarbodiimide.
[0052] When the carbodiimide-based compound is included as an additive, the solid content of the slurry is increased, and it is easy to control the thixotropy of the slurry. For example, when the carbodiimide-based compound is added to an existing composition as an additive to prepare the slurry, the solid content is increased and it is easy to control the thixotropy of the slurry.
[0053] Also, the additive may be included in an amount of 0.01 wt% to 5 wt% based on the total weight of the solid content of the positive electrode slurry composition. Specifically, the content of the additive may be 0.01 wt% or more, 0.1 wt% or more, or 0.3 wt% or more, and 1.5 wt% or less, 3 wt% or less, or 5 wt% or less. If the content of the additive is less than 0.01 wt%, the positive electrode slurry composition may have poor thixotropy, and it may be difficult to form a coating layer having a uniform thickness when the coating speed changes during the coating process. If the content of the additive is more than 5 wt%, the content of the LiCMC thickener may be relatively reduced, and the positive electrode slurry composition may have poor stability, and cracks may occur after the coating layer is formed.
[0054] In addition, the solvent may be used without any particular limitation as long as it can be mixed with the above-mentioned positive electrode active material, conductive material, binder, thickener, and additives to form a positive electrode slurry composition.
[0055] The solvent may include an organic solvent and / or an aqueous solvent. The organic solvent may include at least one selected from the group consisting of N-methyl-2-pyrrolidone (NMP), methoxypropyl acetate, butyl acetate, glycolic acid, butyl ester, butyl glycol, methyl alkyl polysiloxane, alkyl benzene, propylene glycol, xylene, monophenyl glycol, aralkyl-modified methyl alkyl polysiloxane, polyether-modified dimethyl polysiloxane copolymer, polyacrylate, diisobutyl ketone, organic modified polysiloxane, butanol, isobutanol, modified polyacrylate, modified polyurethane, and polysiloxane-modified polymer. The aqueous solvent may include water.
[0056] The solvent may be 55 to 70 wt % based on the total weight of the positive electrode slurry composition. Specifically, the content of the solvent may be 55 wt % or more, or 57 wt % or more, and 65 wt % or less, 67 wt % or less, or 70 wt % or less. If the content of the solvent is less than 55 wt %, the concentration of the positive electrode slurry composition may be too high and hard, making it difficult to uniformly coat the positive electrode slurry composition on the positive electrode current collector, and if the content of the solvent exceeds 70 wt %, the concentration of the positive electrode slurry composition may be too low and run off, making it difficult to control the positive electrode slurry composition in the coating process, and a long drying time may be required after the formation of the coating layer.
[0057] In the present invention, the positive electrode slurry composition may have a thixotropic index T of 0.1 to 0.4, as represented by the following mathematical formula 1:
[0058] Thixotropic index T=(viscosity of the positive electrode slurry composition at a rotation speed of 10 rpm) / (viscosity of the positive electrode slurry composition at a rotation speed of 1 rpm), The viscosity is measured at 25°C.
[0059] The positive electrode slurry composition has thixotropy, which is a property in which the viscosity increases when no shear stress is applied, and the viscosity decreases when a shear stress is applied.
[0060] Based on the principle that when the positive electrode slurry composition is rotated, a shear stress is applied at a shear rate proportional to the rotation speed, the thixotropy was defined using the viscosity of the positive electrode slurry composition at a rotation speed of 10 rpm relative to the viscosity of the positive electrode slurry composition at a rotation speed of 1 rpm, as shown in Equation 1. When the rotation speed is 1 rpm, the shear rate is 0.29 / s, and when the rotation speed is 10 rpm, the shear rate is 2.9 / s.
[0061] If the thixotropy index T is less than 0.1, the viscosity at a high rotation speed is very low compared to a low rotation speed, and the effective coating speed is limited when the coating speed is changed in the process of coating the positive electrode slurry composition on the positive electrode current collector, and if it exceeds 0.4, the viscosity change is not large even when the coating speed is changed, and it may be difficult to respond to the slurry. Specifically, the thixotropy index T may be 0.1 or more, 0.15 or more, or 0.2 or more, and may be 0.3 or less, 0.35 or less, or 0.4 or less.
[0062] Method for producing positive electrode slurry composition for lithium secondary battery The present invention also relates to a method for preparing a positive electrode slurry composition for a lithium secondary battery, the types and weights of materials used in preparing the positive electrode slurry composition being as described above.
[0063] The positive electrode slurry composition may be prepared by adding and mixing the above-mentioned positive electrode active material, conductive material, binder, thickener, and additives to a solvent.
[0064] The mixing may be performed by milling, but is not particularly limited as long as it is a mixing method used in the art for forming a slurry. For example, the milling may be bead milling, roll milling, ball milling, attrition milling, planetary ball milling, jet milling, or screw mixing milling. Preferably, bead milling may be used in consideration of uniform mixing and dispersibility of the components included in the positive electrode slurry composition.
[0065] Positive electrodes for lithium secondary batteries The present invention also provides a positive electrode for a lithium secondary battery, comprising: a positive electrode current collector; and a positive electrode active material layer formed on one surface of the positive electrode current collector, the positive electrode active material layer including a positive electrode active material, a binder, a conductive material, a thickener, and an additive.
[0066] In the present invention, the positive electrode current collector is not particularly limited as long as it has conductivity without inducing chemical changes in the battery and can be used electrochemically stably at the positive electrode charging voltage. For example, the positive electrode current collector may be one or more selected from the group consisting of copper, aluminum, stainless steel, titanium, silver, palladium, nickel, alloys thereof, and combinations thereof. The stainless steel may be surface-treated with carbon, nickel, titanium, or silver.
[0067] In addition, the shape of the positive electrode current collector is not particularly limited, and may be in the form of a film, sheet, foil, net, porous body, foam, or nonwoven fabric. If necessary, the surface of the positive electrode current collector may be formed with fine irregularities, and the irregularities may help improve adhesion to the positive electrode active material layer. The method of forming irregularities on the surface of the positive electrode current collector is not particularly limited, and may be a known method such as mechanical polishing, electrolytic polishing, or chemical polishing.
[0068] The thickness of the positive electrode current collector is not particularly limited and can be set within an appropriate range in consideration of the mechanical strength of the positive electrode, productivity, or battery capacity. For example, the thickness of the positive electrode current collector can usually be 3 μm to 500 μm.
[0069] In the present invention, the positive electrode active material layer is formed by the positive electrode slurry composition as described above, and may include a positive electrode active material, a binder, a conductive material, a thickener, and an additive. The types and contents of the positive electrode active material, the binder, the conductive material, the thickener, and the additive are as described above.
[0070] The thickness of the positive electrode active material layer is not particularly limited and may be set within an appropriate range in consideration of the mechanical strength of the positive electrode, the loading amount, or the capacity of the battery. For example, the thickness of the positive electrode active material layer may typically be 30 μm to 300 μm.
[0071] Method for manufacturing positive electrode for lithium secondary battery The present invention also relates to a method for manufacturing a positive electrode for a lithium secondary battery, the method including: (S1) coating one surface of a positive electrode current collector with the positive electrode slurry composition; (S2) drying the coating layer formed in the (S1) step; and (S3) rolling the coating layer to form a positive electrode active material layer.
[0072] In step (S1), the positive electrode slurry composition may be coated on one surface of a positive electrode current collector to form a coating layer. The positive electrode current collector and the positive electrode slurry composition are as described above.
[0073] The coating method is not particularly limited as long as it can coat the slurry. For example, the coating method may be one or more selected from the group consisting of roll-to-roll coating, spin coating, nozzle printing, inkjet printing, slot coating, and dip coating, and is preferably the roll-to-roll coating method.
[0074] In the coating process using the above coating method, the coating speed may be variable. The coating speed may be changed to establish an optimized drying condition depending on the coating conditions. The reason why the coating speed is variable is that the drying speed of the solvent varies depending on the properties of the positive electrode slurry composition during the process of applying the positive electrode slurry composition to the current collector and drying it.
[0075] In step (S2), the coating layer formed in step (S1) may be dried.
[0076] The drying may cause the solvent contained in the positive electrode slurry composition to evaporate, thereby forming a coating layer in the form of a layer.
[0077] The drying temperature may be 30° C. or more, 40° C. or more, or 45° C. or more, and may be 60° C. or less, 70° C. or less, or 80° C. or less so that a good quality positive electrode active material layer can be formed.
[0078] In step (S3), the coating layer formed in step (S2) may be rolled to form a positive electrode active material layer.
[0079] The rolling may be a typical rolling process used in the art, and may be performed using a roll press. For example, the rolling using a roll press may be performed by applying pressure to the positive electrode current collector on which the coating layer is formed with two rolls arranged on the upper and lower sides of the positive electrode current collector on which the coating layer is formed with the rolls, and simultaneously moving the positive electrode current collector on which the coating layer is formed in a horizontal direction.
[0080] Lithium secondary battery The present invention also relates to a lithium secondary battery including a positive electrode, a negative electrode, a separator, and an electrolyte.
[0081] In the lithium secondary battery according to the present invention, the structure, constituent materials and manufacturing method of the positive electrode are as described above.
[0082] In the lithium secondary battery according to the present invention, the negative electrode may include a negative electrode current collector and a negative electrode active material layer formed on the negative electrode current collector. The negative electrode active material layer (for example, lithium foil) may be used alone.
[0083] The negative electrode current collector is not particularly limited as long as it does not induce a chemical change in the battery and has conductivity, and examples of the negative electrode current collector that can be used include copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. Also, the negative electrode current collector can be in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc., having fine irregularities formed on the surface, similar to the positive electrode current collector.
[0084] In addition, the negative electrode active material may be one or more carbon-based materials selected from the group consisting of crystalline artificial graphite, crystalline natural graphite, amorphous hard carbon, low-crystalline soft carbon, carbon black, acetylene black, ketjen black, super-P, graphene, and fibrous carbon, Si-based materials, LiFeO(0≦x≦1), Lix WO₂(0 ≤ x ≤ 1), Sn x Me 1-x Me’ y O z (Me: Mn, Fe, Pb, Ge; Me’: Al, B, P, Si, Group 1, 2, 3 elements of the periodic table, halogen; 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8) and other metal composite oxides; lithium metal; lithium alloy; silicon-based alloy; tin-based alloy; metal oxides such as SnO, SnO₂, PbO, PbO₂, Pb₂O₃, Pb₃O₄, Sb₂O₃, Sb₂O₄, Sb₂O₅, GeO, GeO₂, Bi₂O₃, Bi₂O₄, Bi₂O₅; conductive polymers such as polyacetylene; Li-Co-Ni-based materials; titanium oxides; lithium titanium oxides, etc. can be included, but are not limited to these only.
[0085] In addition to this, the negative electrode active material is SnₓMe 1-x Me’ y O z (Me: Mn, Fe, Pb, Ge; Me’: Al, B, P, Si, Group 1, 2, 3 elements of the periodic table, halogen; 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8) and other metal composite oxides; oxides such as SnO, SnO₂, PbO, PbO₂, Pb₂O₃, Pb₃O₄, Sb₂O₃, Sb₂O₄, and Bi₂O₅ can be used, and carbon-based negative electrode active materials such as crystalline carbon, amorphous carbon, or carbon composites can be used alone or in combination of two or more.
[0086] In the lithium secondary battery according to the present invention, all of those that have been commonly used in the manufacture of lithium secondary batteries can be used as the electrolytic solution.
[0087] The lithium salts that can be included as electrolytes in the electrolytic solution can be used without limitation those that are commonly used in electrolytic solutions for lithium secondary batteries. For example, as the anions of the lithium salts, F - , Cl - , Br - , I - , NO₃ - , N(CN)₂- , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - , and (CF3CF2SO2)2N - The lithium salt may be any one selected from the group consisting of: The lithium salt may be LiTFSI (Lithium bis(trifluoromethanesulfonyl)imide, LiC2F6NO4S2) and / or LiNO3.
[0088] In the electrolyte used in the present invention, the organic solvent contained in the electrolyte may be any organic solvent commonly used in electrolytes for lithium secondary batteries without limitation. According to one embodiment of the present invention, the organic solvent may be a carbonate-based, ester-based, ether-based, ketone-based, alcohol-based, or aprotic solvent. Among them, an ether-based solvent may be typically used.
[0089] Specific examples of the carbonate-based solvent include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), and the like.
[0090] Specific examples of the ester solvent include methyl acetate, ethyl acetate, n-propyl acetate, 1,1-dimethylethyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, decanolide, valerolactone, mevalonolactone, and caprolactone.
[0091] Specific examples of the ether solvent include dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether, ethyl propyl ether, dimethoxyethane, diethoxyethane, methoxyethoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, triethylene glycol dimethyl ether, triethylene glycol diethyl ether, triethylene glycol methyl ethyl ether, tetraethylene glycol dimethyl ether, tetraethylene glycol diethyl ether, tetraethylene glycol methyl ethyl ether, polyethylene glycol dimethyl ether, polyethylene glycol diethyl ether, polyethylene glycol methyl ethyl ether, diglyme, triglyme, tetraglyme, tetrahydrofuran, 2-methyltetrahydrofuran, and polyethylene glycol dimethyl ether.
[0092] The ketone solvent may be, for example, cyclohexanone, etc. The alcohol solvent may be, for example, ethyl alcohol, isopropyl alcohol, etc.
[0093] Specific examples of the aprotic solvent include nitriles such as acetonitrile, amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane (DOL), and sulfolane.
[0094] The non-aqueous organic solvent may be used alone or in combination of two or more thereof. When two or more thereof are used in combination, the mixing ratio may be appropriately adjusted depending on the desired battery performance.
[0095] In the lithium secondary battery according to the present invention, the separator may be a conventional porous polymer film used as a separator in the art. For example, the separator may be a porous polymer film made of a polyolefin polymer such as polyethylene, polypropylene, ethylene / butene copolymer, ethylene / hexene copolymer, ethylene / methacrylate copolymer, etc., either alone or in a laminated state, or a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high melting point glass fiber, polyethylene terephthalate fiber, etc., but is not limited thereto.
[0096] In the lithium secondary battery according to the present invention, the battery form is not particularly limited, and may be, for example, a jelly-roll type, a stick type, a stack-folding type (including a stack-Z-folding type), or a lamination-stick type, and preferably a stack-folding type.
[0097] In addition, the lithium secondary battery may be manufactured by sequentially stacking the negative electrode, the separator, and the positive electrode to prepare an electrode assembly by injecting an electrolyte solution, placing the electrode assembly in a battery case, and assembling the battery case by sealing it with a cap plate and a gasket.
[0098] At this time, lithium secondary batteries can be classified into various types of batteries such as lithium-sulfur secondary batteries, lithium-air batteries, lithium-oxide batteries, and lithium solid-state batteries depending on the materials of the positive and negative electrodes used, and can be classified into cylindrical, square, coin, and pouch types depending on the shape, and can be classified into bulk and thin film types depending on the size. The structure and manufacturing method of these batteries are widely known in this field, so detailed description will be omitted.
[0099] In the present invention, the lithium secondary battery may be a lithium-sulfur secondary battery using a cathode material containing a sulfur-carbon composite as a cathode. The lithium-sulfur secondary battery may use lithium metal as an anode active material. When the lithium-sulfur secondary battery is discharged, an oxidation reaction of lithium occurs at the anode, and a reduction reaction of sulfur occurs at the cathode. At this time, the reduced sulfur combines with lithium ions transferred from the anode to be converted into lithium polysulfide, which is followed by a reaction to finally form lithium sulfide.
[0100] The present invention also relates to a battery module including the lithium secondary battery, which can be used as a power source for devices that require high capacity and high rate characteristics, etc. Specific examples of the devices include, but are not limited to, power tools that are driven by a battery-type motor; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), etc.; electric two-wheeled vehicles, including electric bicycles (E-bikes) and electric scooters; electric golf carts; and power storage systems.
[0101] Hereinafter, preferred examples will be presented to aid in understanding the present invention. However, the following examples are merely illustrative of the present invention, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical ideas of the present invention. Naturally, such changes and modifications fall within the scope of the appended claims.
[0102] Example 1 (1) Preparation of Positive Electrode Slurry Composition A mixture was obtained by mixing the positive electrode active material, conductive material, binder, thickener, and additive in a weight ratio of 92:5:2:0.7:0.3. The positive electrode active material was an S / CNT composite obtained by mixing sulfur S (Sigma-Aldrich product) with CNT (Carbon Nanotube) using a ball mill and then heat-treating at 155°C. The conductive material was Denka black, the binder was styrene-butadiene rubber (SBR), the thickener was LiCMC (LiCMC1000, GM Chem), and the additive was 1-ethyl-3-[3-(dimethylamino)propyl]-carbodiimide hydrochloride (EDC).
[0103] The mixture was mixed with water to prepare a positive electrode slurry composition.
[0104] (2) Manufacturing of positive electrodes The positive electrode slurry composition was coated on one side of a positive electrode current collector made of aluminum foil having a thickness of 12 μm, dried at 50° C. for 2 hours, and rolled to prepare a positive electrode having a positive electrode active material layer.
[0105] (3) Manufacture of lithium-sulfur secondary batteries A porous polyethylene separator having a thickness of 20 μm and a porosity of 45% was placed between the positive electrode and the lithium negative electrode and placed inside the case, and an electrolyte was injected into the case to prepare a lithium-sulfur secondary battery in the form of a CR-2032 coin cell.
[0106] The electrolyte used was a mixed solvent of 1,3-dioxolane (DOL) and 1,2-dimethoxyethane (DME) (1:1, v / v) to which 0.38 M LiTFSI and 0.31 M LiNO3 were added.
[0107] Comparative Example 1 A positive electrode slurry composition, a positive electrode, and a lithium-sulfur secondary battery were prepared in the same manner as in Example 1, except that no additive was used and the positive electrode active material, the conductive material, the binder, and the thickener were mixed in a weight ratio of 92:5:2:1.
[0108] Experimental Example 1: Measurement of viscosity, thixotropy index and rheological properties of positive electrode slurry composition The viscosities of the positive electrode slurry compositions prepared in the examples and comparative examples were measured, and the thixotropic index was calculated from the measured viscosities. The thixotropic properties were measured, and the results are shown in Table 1 and FIG. 1.
[0109] The method for measuring the viscosity, the method for calculating the thixotropic index, and the method for measuring the rheological properties are as described below.
[0110] (1) Viscosity measurement 4 ml of the positive electrode slurry composition was poured into a container at 25° C., and an SCP-16 spindle (Brookfield) was attached to the container. The SCP-16 spindle was then rotated at speeds of 1 rpm to 10 rpm, and the viscosity (cP) measured at each rotation speed was recorded. A Viscometer (DV2T, Brookfield) was used as the viscometer for viscosity measurement.
[0111] (2) Calculation of the thixotropic index The thixotropic index of the positive electrode slurry composition was calculated using the following mathematical formula 1:
[0112] Thixotropic index T=(viscosity of the positive electrode slurry composition at a rotation speed of 10 rpm) / (viscosity of the positive electrode slurry composition at a rotation speed of 1 rpm),
[0113] The viscosity is measured at 25°C.
[0114] (3) Measurement of flow properties 1 g of the positive electrode slurry composition was placed in a rheometer (DHR-1, TA instruments), and the shear stress (Pa) corresponding to a shear rate varying in the range of 0.1 / s to 50 / s was measured.
[0115] [Table 1]
[0116] As shown in Table 1, Example 1 is a positive electrode slurry composition containing an appropriate amount of EDC as an additive, and has high viscosity and a low thixotropy index value compared to Comparative Example 1, showing high thixotropy.
[0117] Moreover, Comparative Example 1 is a positive electrode slurry composition containing no additives, and although it has the viscosity necessary for forming a slurry, it is understood that it has a low ability to respond to changes in shear stress.
[0118] FIG. 1 is a graph showing the change in shear stress depending on the shear rate for the positive electrode slurry compositions of Example 1 and Comparative Example 1.
[0119] Referring to FIG. 1, the difference in the area inside the hysteresis loop can be seen, which indicates that the slurry of Example 1 has excellent thixotropic properties.
[0120] Experimental example 2: Evaluation of charge / discharge characteristics The lithium-sulfur secondary batteries in the form of CR-2032 coin cells prepared in the examples and comparative examples were subjected to 0.1C charge / 0.1C discharge three times and 0.3C charge / 0.5C discharge within a voltage range of 1.8V to 2.5V to evaluate charge / discharge characteristics.
[0121] FIG. 2 is a graph showing the charge / discharge characteristics of the lithium-sulfur secondary batteries of Example 1 and Comparative Example 1.
[0122] 2, the lithium-sulfur secondary battery of Example 1 exhibited an initial discharge capacity of 1105 mAh / g, which was higher than the discharge capacity of Comparative Example 1 of 1080 mAh / g, and exhibited a life performance of maintaining a discharge capacity of 800 mAh / g or more for more than 100 cycles. This is a performance equivalent to or superior to the discharge capacity maintenance of the lithium-sulfur battery of Comparative Example 1 that does not contain an additive.
[0123] Although the present invention has been described above with reference to limited embodiments and drawings, the present invention is not limited thereto, and it is of course possible for a person having ordinary skill in the art to which the present invention pertains to make various modifications and variations within the technical spirit of the present invention and the equivalent scope of the claims set forth below.
Claims
1. A positive electrode slurry composition for a lithium secondary battery, comprising a positive electrode active material, a conductive material, a binder, a thickener, an additive, and a solvent, The thickening agent includes lithiated carboxymethyl cellulose (LiCMC), The additive includes a carbodiimide compound, The thickener is included in an amount of 0.5 wt % to 5 wt % based on the total weight of the solid content of the positive electrode slurry composition, The additive is contained in an amount of 0.01 wt % to 5 wt % based on the total weight of the solid content of the positive electrode slurry composition.
2. The carbodiimide compound is 1-ethyl-3-[3-(dimethylamino)propyl]-carbodiimide hydrochloride.
2. The positive electrode slurry composition for lithium secondary batteries according to claim 1, comprising at least one selected from the group consisting of N,N'-dimethylaminopropyl hydrochloride, EDC), 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, N,N'-diisopropylcarbodiimide, and N,N'-di-tert-butylcarbodiimide.
3. The solvent may include at least one selected from an organic solvent and an aqueous solvent. The organic solvent includes at least one selected from the group consisting of N-methyl-2-pyrrolidone (NMP), methoxypropyl acetate, butyl acetate, glycolic acid, butyl ester, butyl glycol, methylalkyl polysiloxane, alkylbenzene, propylene glycol, xylene, monophenyl glycol, aralkyl-modified methylalkyl polysiloxane, polyether-modified dimethyl polysiloxane copolymer, polyacrylate, diisobutyl ketone, organic modified polysiloxane, butanol, isobutanol, modified polyacrylate, modified polyurethane, and polysiloxane-modified polymer; The positive electrode slurry composition for lithium secondary batteries according to claim 1 , wherein the aqueous solvent contains water.
4. The positive electrode active material is elemental sulfur (S 8 ), Li 2 S n (n≧1, n is an integer), organic sulfur compounds, and carbon-sulfur polymers [(C 2 S x ) n , 2.5≦x≦50, n≧2, where x and n are integers.
5. 2. The positive electrode slurry composition for lithium secondary batteries according to claim 1, wherein the positive electrode slurry composition has a thixotropic index (T) of 0.1 to 0.
4.
6. a positive electrode current collector; and a positive electrode active material layer formed on one surface of the positive electrode current collector, A positive electrode for a lithium secondary battery, wherein the positive electrode active material layer is formed from the positive electrode slurry composition according to claim 1 .
7. (S1) coating one surface of a positive electrode current collector with the positive electrode slurry composition of claim 1; (S2) drying the coating layer formed in (S1); and (S3) rolling the coating layer to form a positive electrode active material layer.
8. 8. The method of claim 7, wherein the coating is performed using at least one selected from the group consisting of bar coating, roll-to-roll coating, spin coating, nozzle printing, inkjet printing, slot coating, and dip coating.
9. A lithium secondary battery comprising the positive electrode according to claim 6, a negative electrode, a separator, and an electrolyte.
10. The lithium secondary battery according to claim 9, wherein the lithium secondary battery is a lithium-sulfur secondary battery.
Citation Information
Patent Citations
Nonaqueous electrolyte battery
JP1998154513A
Non-aqueous electrolyte secondary battery
JP2001143711A
Slurry composition for secondary battery use, binding resin composition for secondary battery positive electrode use, binding resin composition for secondary battery negative electrode use, binding resin composition for secondary battery separator porous film use, and binding resin composition for secondary battery electrode porous film use
JP2014060149A
Method for manufacturing electrode plate of nonaqueous electrolyte secondary battery, method for manufacturing electrode assembly of nonaqueous electrolyte secondary battery, and method for manufacturing nonaqueous electrolyte secondary battery
JP2014203561A
Electrode for secondary battery, and manufacturing method thereof, and secondary battery
JP2014232708A